The correct procedure is
[tex] \sqrt{x+6} -4=x \\ \sqrt{x+6} =x+4 \\ x+6=(x+4)^{2} \\x+6=x^{2}+8x+16 \\0=x^{2}+7x+10[/tex]
This quadratic equation factorizes into
(x + 5)(x + 2) = 0
x = -5 or x = -2.
It is customary to plug the two solutions back into the original equation in order to reject extraneous solutions.
When x = -5,
√(x+6) = 1
x+4 = 1
Accept this solution.
When x = -2,
√(x+6) = 2
x+4 = 2
Accept this solution.
Answer:
Israel solved the problem correctly by obtaining x = -2, -5, but he did not check for extraneous solutions